BIFIDOGENIC PROPERTIES OF A BIOTECHNOLOGICAL ANALOGUE OF HUMAN LACTOFERRIN - Ilya B. Brodsky; Andrey V. Vasiliev; A. V. Kopychenkova; Igor L. Goldman; Petr Е. Sadchikov; Leyla S. Namazova-Baranova; Тatyana E. Borovik; Olga L. Lukoyanova; G. V. Yatsyk; E. R. Sadchikova (Union of pediatricians of Russia, 2017)
Background:  Recent research shows that the growth and development of the gastrointestinal  tract of children fed by breast milk is more intense than that of the formula fed, since the human lactoferrin contained in the breast milk is a factor that stimulates cell growth. Therefore, the possibility of using exogenous lactoferrin will be of great importance in the nutrition of infants.Objektive: To study the bifidogenic properties of the biotechnological analogue of human lactoferrin. Methods: Kinetics of growth and CFU titer of bifidobacterial culture in the presence of a biotechnological analogue of human lactoferrin (0,05-5 mg /ml) was determined.Results: It has been shown that different concentrations of the protein can have both a stimulating (for B. bifidum and B. infantis) and inhibitory (for B. longum) effect on the growth of bifidobacteria, which is due to the affinity of lactoferrin binding to them. It seems important to further study the stimulating effect of this protein on the growth of lactobacilli in the intestine of the child.Conclusion:  Due to bifidogenic and high bactericidal action, lactoferrin can be effective in feeding newborns.